A Review of Traditional Environmental Knowledge: An Interdisciplinary Canadian Perspective - G. Kuhn, Richard; Duerden, Frank (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1996)
Over the past fifteen years there has been increasing interest in the nature and application of Traditional Environmental Knowledge (TEK) in Canada. This lias coincided with the settlement of land claims, the emergence of comanagement regimes, and the ascendancy of First Nation power and influence in formal decision making processes. Discourses on actual and potential applications of TEK in land and resource management are the focus of this paper. TEK is the outcome of complex interactions between a culture and the natural environment. Although there are different cosmologies and adaptations, common themes emerge in the way knowledge is acquired and communicated. There is also a great deal of value in its application. However, a number of issues remain to be resolved such as the compatibility between Western scientific knowledge and TEK, and the acquisition and application of TEK by "outsiders." As knowledge is taken from its immediate context it is "abstracted" to conform with the needs of the user and to the scale at which it is being applied. Two subsequent issues emerge. First, TEK is transformed as it is removed from its original context, and second, it may be co-opted in the name of resource and land management decisions that do not necessarily serve First Nations’ interests.